Targets of opportunity : on the militarization of thinking - Weber, Samuel, 1940- (Book collections on Project MUSE., 2005)
A study of targeting, Weber also traces the emergence of an alternative to targeting, first within military and strategic thinking itself and then using the work of Walter Benjamin.